Kinetics and Equilibrium Models for the Adsorption of Thiosulfate and Polythionates onto Strong Base Anion Exchange Resin in Batch System - Muslim, Abrar (2009)
Kinetic and equilibrium models for the isotherm adsorption of thiosulfate and polyhionate on resin have been developed using mechanistic approach. The models can be used to predict amount of species adsorbed on resin over time and at the equilibrium. Experimental work has been done, and the results are used to validate the models. Lagergren, Ho and Freundlich models are addressed in the results to challenge the developed models. As the results, parameters needed for the isotherm adsorption model are established. Overall, the model-based results are in a good agreement with the experimental results.